2017
DOI: 10.1017/s0954579417001687
|View full text |Cite
|
Sign up to set email alerts
|

Maternal smoking during pregnancy and offspring executive function: What do we know and what are the next steps?

Abstract: Children exposed to maternal smoking during pregnancy (MSDP) exhibit difficulties in executive function (EF) from infancy through adolescence. Due to the developmental significance of EF as a predictor of adaptive functioning throughout the life span, the MSDP-EF relation has clear public health implications. In this paper, we provide a comprehensive review of the literature on the relationship between MSDP and offspring EF across development; consider brain-based assessments, animal models, and genetically in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 149 publications
(233 reference statements)
1
10
0
Order By: Relevance
“…For example, there is evidence about the effects of prenatal adversity such as stress, toxicants, substance abuse, and nutrition on disruptive child behavior, possibly through epigenetic effects, brain development, and temperament . The fetal environment has also received attention, for example, maternal smoking has been associated with child executive function and links between neonatal DNA methylation and early onset conduct disorders have been examined . Psychophysiological correlates of aggressive behavior in the form of brain dysfunction and impairments in brain systems have been identified …”
Section: Resultsmentioning
confidence: 99%
“…For example, there is evidence about the effects of prenatal adversity such as stress, toxicants, substance abuse, and nutrition on disruptive child behavior, possibly through epigenetic effects, brain development, and temperament . The fetal environment has also received attention, for example, maternal smoking has been associated with child executive function and links between neonatal DNA methylation and early onset conduct disorders have been examined . Psychophysiological correlates of aggressive behavior in the form of brain dysfunction and impairments in brain systems have been identified …”
Section: Resultsmentioning
confidence: 99%
“…Effects on newborn attention complement prior cross-sectional and longitudinal studies of prenatal TOB (Espy et al, 2011; Mansi et al, 2007). Although effects of prenatal TOB have been somewhat inconsistent in early infancy (Law et al, 2003; Stroud et al, 2009b; Yolton et al, 2009), one of the more consistent long-term effects of prenatal TOB is its association with child attention deficits, ADHD, and deficits in executive function (Huang et al, 2018; Micalizzi and Knopik, 2017). In contrast, prior studies of prenatal MJ did not show effects on attention in the newborn period (de Moraes Barros et al, 2006; Fried, 1980; Fried and Makin, 1987), although effects on long-term attention and executive function deficits have been shown (El Marroun et al, 2011; Smith et al, 2006; Smith et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…First of all, a review has shown that children who have been exposed to both prenatal maternal alcohol use and a traumatic event are more likely to show deficits in attention, memory, intelligence and increased behavioral problems (Price et al, 2017). Second, prenatal exposure to cannabis or cigarettes is also related with problems in executive functioning in both young and older children (Fried & Smith, 2001;Micalizzi & Knopik, 2018;Noland et al, 2003;Richardson et al, 2002). Third, previous research suggested that parents' educational level is negatively associated with executive functioning (Ardila et al, 2010) and that a low educational level is a risk factor for trauma exposure (Brattström et al, 2015).…”
Section: Parenting Behaviormentioning
confidence: 99%